Suffragettes : a story of three women - Colmore, G. (Gertrude), 1855-1926 (London : Pandora Press, 1984)
Sally, Edith, and Geraldine, three New Englanders from completely different backgrounds, find a common cause in the Women's Suffrage Movement.
Originally published as: Suffragette Sally. 1911.
Keywords: Women -- Great Britain -- Fiction; Women -- Suffrage -- Fiction